A chromatographic method to monitor fructan catabolism in two cool‐season grasses fermented by mixed bovine ruminal microbiota. Issue 6 (12th May 2022) - Kagan, Isabelle A.; Harlow, Brittany E.; Flythe, Michael D.
Abstract: BACKGROUND: Cool‐season grasses contain fructans (fructose‐based polymers), whose monomers are linked by β‐2, 6 or β‐1, 2 bonds. Fructans in the rumen are hydrolysed to fructose by bacterial enzymes, but little is known about the kinetics of fructan catabolism in the rumen. A chromatographic method, using high‐performance anion‐exchange chromatography (HPAEC) with pulsed amperometric detection, was developed to monitor changes in fructan profiles during the in vitro fermentation of timothy ( Phleum pratense L.) and cocksfoot ( Dactylis glomerata L.) by mixed rumen microbes. Sterile suspensions of freeze‐dried and milled tissue in minimal media were inoculated with washed rumen microbial cells under anaerobic conditions, and aliquots of the incubations were profiled 0, 2, and 5 h post‐inoculation. RESULTS: Timothy and cocksfoot differed in initial concentrations of glucose and sucrose, and in the amounts remaining 2 h post‐inoculation ( p  < 0.01). The grasses also differed in initial concentrations of short‐chain fructan, and in concentrations present 2 h post‐inoculation ( p  = 0.01). Timothy and cocksfoot also differed in amounts of long‐chain fructans remaining 2 and 5 h post‐inoculation ( p  = 0.03), and in the maximum degree of polymerisation after 2 h ( p  < 0.01). CONCLUSIONS: Over the first 2 h, long‐chain fructans in cocksfoot decreased while short‐chain fructans increased. In timothy, concentrations of short‐chain fructans doubled, and the degree of polymerisation decreased by 15%. The results support a model of degradation of the longest fructan chains and conversion into shorter ones.